2015
DOI: 10.1080/10810730.2015.1018637
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Tool Effectiveness for Older Patients: A Systematic Review of the Literature

Abstract: Online health information tools (OHITs) have been found to be effective in improving health outcomes. However, the effectiveness of these tools for older patients has been far from clear. This systematic literature review therefore provides an overview of online health information tool effectiveness for older patients using a two-dimensional framework of OHIT functions (i.e., providing information, enhancing information exchange, and promoting self-management) and outcomes (i.e., immediate, intermediate, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 48 publications
(165 reference statements)
1
44
2
Order By: Relevance
“…• General-purpose information technologies, including mobile communications (Fry and Neff, 2009;Bolle et al, 2015;Blackman et al 2013;Geraedts et al, 2013;Buchholz, Wilbur, Ingram and Fogg, 2013;Foster et al, 2013;Buhi et al 2013;Chen and Schulz, 2016), messaging (e.g. mail or chat) (Foster et al, 2013), (Kennedy et al, 2012;Hawley-Hague et al, 2014).…”
Section: Total Number Of Articles (N=24)mentioning
confidence: 99%
See 3 more Smart Citations
“…• General-purpose information technologies, including mobile communications (Fry and Neff, 2009;Bolle et al, 2015;Blackman et al 2013;Geraedts et al, 2013;Buchholz, Wilbur, Ingram and Fogg, 2013;Foster et al, 2013;Buhi et al 2013;Chen and Schulz, 2016), messaging (e.g. mail or chat) (Foster et al, 2013), (Kennedy et al, 2012;Hawley-Hague et al, 2014).…”
Section: Total Number Of Articles (N=24)mentioning
confidence: 99%
“…Physical Activity (Fry and Neff, 2009;Kennedy et al, 2012;Blackman et al 2013;Geraedts et al, 2013;Buchholz et al, 2013;Foster et al, 2013;Bort-Roig et al, 2014;Mateo et al, 2015;Bert et al, 2014;Matthews et al, 2016;Beishuizen et al, 2016) Nutrition and Weight Management (Fry & Neff, 2009;Ngo et al, 2009;Kelders et al, 2011;Lieffers and Hanning, 2012;Vegting et al, 2014;Mateo et al, 2015;Laranjo et al, 2014;Bardus et al, 2015;Bert et al, 2014) Health Education (Fox, 2009;Kennedy et al, 2012;Bolle et al, 2015;Buhi et al 2013;Moorhead et al, 2013;Laranjo et al, 2014;Bert et al, 2014;Shingleton and Palfai, 2016 …”
Section: Scope Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…New media play an increasing role in the everyday life even for older individuals, as they extensively use the Internet, patient portals, and mobile phone applications to search for health-related information 14. In a systematic review, Bolle et al14 found that Internet-based information tools might be effective in improving self-efficacy in older patients.…”
Section: Introductionmentioning
confidence: 99%